Hypopituitarism in children with cerebral palsy. Issue 6 (27th October 2016) - Uday, Suma; Shaw, Nick; Krone, Ruth; Kirk, Jeremy
Abstract : Poor growth and delayed puberty in children with cerebral palsy is frequently felt to be related to malnutrition. Although growth hormone deficiency is commonly described in these children, multiple pituitary hormone deficiency (MPHD) has not been previously reported. We present a series of four children with cerebral palsy who were born before 29 weeks gestation who were referred to the regional endocrinology service, three for delayed puberty and one for short stature, in whom investigations identified MPHD. All patients had a height well below −2 standard deviation score (2nd centile) at presentation and three who had MRI scans had an ectopic posterior pituitary gland. We therefore recommend that the possibility of MPHD should be considered in all children with cerebral palsy and poor growth or delayed puberty. Early diagnosis and treatment is essential to maximise growth and prevent associated morbidity and mortality.